Entre o nomos e o nome : o discurso identitário na comunidade quilombola de Malhadinha (Tocantins – Brasil) - Nascimento, Ariel Elias do (2020)
This thesis aims to understand the processes that involve the formation of the quilombola identity of the Malhadinha quilombola community, located in the State of Tocantins. The investigative process of this Thesis starts from the analysis of the concepts of heterotopia and heterochrony present in the text of Michel Foucault. These concepts are important to think about other discursive possibilities about quilombola identity in the final years of the 20th century. The problem to be followed in the Thesis is based on the close relationship between the real world and the imaginary world. So, is the identity that presents itself the same constructed identity? The methodology used in this Thesis is the bibliographic and documentary review, where concepts such as biopower, ecosophy, sameness, resilience and neocommunity configure the argumentative locus for the perception of space and the anthropic relationships established there. The results achieved prove that the quilombola identity of the Malhadinha society was influenced by two factors that are present in the studied period: on the one hand, the letter of the law in the Federal Constitution of 1988 and, on the other hand, the organization of an association of small producers rural areas in 1993. The analysis of these two points is necessary to understand the becoming quilombola from 2006, the year in which the transformation of the Village into the Quilombola Community occurs.